1992
DOI: 10.1093/nar/20.4.851
|View full text |Cite
|
Sign up to set email alerts
|

The primary transcription unit of the human (eqn)a2 globin gene defined by quantitative RT/PCR

Abstract: We have set up an experimental system to map the primary transcription unit of the human alpha 2 globin gene. The duplicated human alpha globin genes (alpha 2-alpha 1) were linked to the alpha globin locus Positive Regulatory Element (PRE) and stably transfected into murine erythroleukaemia cells. We then developed a quantitative reverse transcriptase, polymerase chain reaction assay to map alpha 2 primary transcripts using primer pairs derived from different parts of the alpha 2 globin gene and its 3' flankin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Radioactive PCR products were excised and quantitated. The radioactivity of each PCR product is given as a percentage of that recorded for the PCR product produced with oligonucleotide 1. between RNA input and PCR product was determined, as described in Owczarek et al (1992) and was found to exist after 20 cycles of amplification, for 50 ng of S.pombe RNA (data not shown). Therefore a measure of the relative number of transcripts was made by comparing the counts incorporated into the PCR products separated electrophoretically ( Figure 2B) after 20 cycles and is presented in Figure 2A.…”
Section: Resultsmentioning
confidence: 99%
“…Radioactive PCR products were excised and quantitated. The radioactivity of each PCR product is given as a percentage of that recorded for the PCR product produced with oligonucleotide 1. between RNA input and PCR product was determined, as described in Owczarek et al (1992) and was found to exist after 20 cycles of amplification, for 50 ng of S.pombe RNA (data not shown). Therefore a measure of the relative number of transcripts was made by comparing the counts incorporated into the PCR products separated electrophoretically ( Figure 2B) after 20 cycles and is presented in Figure 2A.…”
Section: Resultsmentioning
confidence: 99%
“…The first to be characterized was the ␣2 element (30), which very likely acts as an auxiliary element in poly(A)-dependent termination (61). In one report, run-on transcription of the cloned ␣2 gene showed pausing in the neighborhood of this element but no termination that was poly(A)-dependent (30).…”
Section: Poly(a)-dependent Pausing As a Checkpoint For Coupling Procementioning
confidence: 99%
“…More likely, as previously described for the CCAAT sequence (51) these elements operate as weak poly(A)-independent terminators when acting alone. Thus, whereas the ␣2 and C2 elements undoubtedly activate poly(A) signals (30,60,63) and probably also termination (30,60,61) and possibly even splicing (64), there is no consistent evidence that they actually pause RNA polymerase II in vivo or that their function is related to pausing.…”
Section: Poly(a)-dependent Pausing As a Checkpoint For Coupling Procementioning
confidence: 99%
“…A few studies, however, have identified defined termination sequences at which efficient transcription termination occurs (Enriquez-Harris et al 1991;Owczarek et al 1992;Tantravahi et al 1993). These sequences are different in different genes, but a common feature is an A-rich region.…”
Section: Termination Of Transcriptionmentioning
confidence: 99%